PERAN BIANG KAMPUNG MENOLONG IBU HAMIL MELAHIRKAN DI KELURAHAN BAILANG KECAMATAN BUNAKEN KOTA MANADO - Haerani, Dolfin Ratuawati Haerani Ratuawati; Tasik, Femmy; Goni, Syirley (Sam Ratulangi University, 2017)
Health is the main capital of the nation's progress because every citizen of Indonesia isentitled to health services. Health problems for residents in the city as well as in ruralIndonesia are still a problem that still exists to this day. It can be seen from the number ofhealth programs that are implemented and continue to be developed has not run well,whether it is a new health program or health program results modification of the oldprogram. One program that has not reached the target as expected is delivery help. Almostthroughout Indonesia there are still many deliveries assisted by the village cultivators.II. The purpose of this research is to know the role of the village custodian to help pregnantmother give birth in Bailang Village, Bunaken Sub-district, Manado City.The method used by researchers is qualitative research. Researchers want to know theattitude of the community, family, pregnant women, especially the village culprit helpmothers give birth. As for this research take informant which is focus of this research is 5months pregnant mother 1 person, pregnant mother 7 month 1 person, pregnant mother 8month 1 person, mother giving birth by one of the villager cultivator, village culprit Train ,Midwife 1 person (as pengelolah program), family companion 1 person, Key informant whodomiciled in Kelurahan Bailang District Bunaken 1 person. The research has been conductedfor 2 months, starting from June to July 2017 in Bailang Village, Bunaken Sub-district,Manado City.Delivery aid by a non-medical health worker is performed by a person who is called a villageculprit, a prelim village culprit is a person who is considered skilled and trusted by thecommunity to help mother and child deliveries and care according to the needs of thecommunity. The community's belief in the skill of the village master is related to the culturalvalues of the local community. Usually the village culprit helps the delivery without regard tosafety, hygiene and mechanisms as it should be so that various complications can result indeath. Basically a village culprit, based on the belief of the local community or is a work thathas been passed down from generation to ancestor or family and usually have aged Â± 40years and over. This research would like to highlight the social life of coastal communitieslearned from the existence of coastal communities in which it contains elements of theinstitutions. The theory used in this research is role theory.The results obtained cultural traditions of pregnant women based on hereditary culturesfrom parents to the generation of pregnant women have been accustomed and also thebelief to the village cultivator in taking the choice because pregnant women feel moreconfident to the village culprit in assisting labor using ritual (customs) in terms of sevenmonthlyprayer reads of pregnancy. The village cultivator can not assess the risks of veryyoung pregnant women and the age of high risk pregnant women. The village cultivator inhelping delivery has knowledge in terms of experience not based on education, becauseeducation is only a village cultivation graduates SR (Sekolah Rakyat / SD-level) and some areliterate.